Charge‐Transfer States at Organic–Organic Interfaces: Impact of Static and Dynamic Disorders. Issue 14 (14th February 2019) - Zheng, Zilong; Tummala, Naga Rajesh; Wang, Tonghui; Coropceanu, Veaceslav; Brédas, Jean‐Luc
Abstract: Molecular dynamics simulations are combined with density functional theory calculations to evaluate the impact of static and dynamic disorders on the energy distribution of charge‐transfer (CT) states at donor–acceptor heterojunctions, such as those found in the active layers of organic solar cells. It is shown that each of these two disorder components can be partitioned into contributions related to the energetic disorder of the transport states and to the disorder associated with the hole–electron electrostatic interaction energies. The methodology is applied to evaluate the energy distributions of the CT states in representative bulk heterojunctions based on poly‐3‐hexyl‐thiophene and phenyl‐C61 ‐butyric‐acid methyl ester. The results indicate that the torsional fluctuations of the polymer backbones are the main source of both static and dynamic disorders for the CT states as well as for the transport levels. The impact of static and dynamic disorders on radiative and nonradiative geminate recombination processes is also discussed. Abstract : In organic solar cells, energetic disorder has a major impact on the charge‐recombination rates and thus on open‐circuit voltage losses. In poly‐3‐hexyl‐thiophene (P3HT):[6, 6]‐phenyl‐C61‐butyric‐acid methyl ester amorphous heterojunctions, the torsional flexibility of the P3HT backbones is seen as the main origin of the large dynamic and static disorders impacting both charge‐transfer and transport states.